Reactivity of Chromium with Aluminates: The Quest for Monovalent Chromium Complexes - HajiAli Afzali, Saba (Université d'Ottawa / University of Ottawa, 2013)
Progress in catalytic ethylene oligmerization and polymerization processes creates an enormously valuable and active field in both industry and academic perspective. From the naive point of view, gathering ethylene molecules to generate carbon carbon bonds can be assumed as the no electron, no energy and facile chemical process which results from interaction of several π-electrons but this process never can afford macro- and micromolecule without applying catalysts. It is no wonder that major efforts have been committed to designing novel catalysts to perform poly- and oligomerization processes, both recently and in the past which provide the extensive library of catalysts today. Among all the metals applied in preparation of homogeneous catalysts for ethylene oligo- and polymerization, chromium has been ideal in providing versatile systems in terms of selectivity and activity for oligomer and polymer productions. In the first part of the current work we chose two different ligand systems (iminopyridine and bisiminophosphine) to investigate the activity of their chromium complexes for ethylene oligmerization and polymerization at different conditions. In addition we took on the substantial challenge of explaining the activities through isolation of intermediates during the catalytic runs. The major focus in this part was rationalizing catalytic behaviour of the catalysts through elucidation of metal oxidation state. To fulfill this goal, syntheses of chromium-aluminate complexes in different valence states as well as description ligand-metal interactions were presented. In the second part of this thesis, our mainly focus of study was on the development in the well- established field of radical chemistry of alkylaluminum. Preferential cation radical and diradical formation and exploring their stabilities through both experimental and computational methods will be discussed. Also continuation of this work led us to report unprecedented double alkylation on the ligand system.